A single tertiary centre outlook on the short-term outcome of bariatric surgery in improving pulmonary parameters and sleep apnoea. (June 2021) - Mohd Nasir, Ahmad Adib Bin; Ban, Andrea Yu-Lin; Syed Zakaria, Syed Zulkifli; Nik Mahmood, Nik Ritza Kosai; Abdul Hamid, Mohamed Faisal
Background: Obesity is associated with obstructive sleep apnoea (OSA). Weight loss is an effective treatment. Bariatric surgery for obese, symptomatic OSA patients results in weight loss and improvement in lung function and sleep apnoea. This study aimed to determine the effectiveness of bariatric surgery in improving the respiratory mechanics and sleep apnoea using a lung function test and sleep study. Methods: A prospective study was conducted at the Pusat Perubatan Universiti Kebangsaan Malaysia Medical Centre involving adults undergoing bariatric work-up, attending respiratory clinic or admitted for bariatric work-up. We included subjects with a body mass index (BMI) >35 kg/m 2 and Apnoea–Hypopnoea Index (AHI) of >5 events/hour. Subjects were assessed at baseline and at 12±2 weeks post bariatric surgery using the following methods: a partial sleep study, lung function test, six-minute walk test (6MWT) and Epworth Sleepiness Scale (ESS) score. Results: Twelve subjects were analysed. Their mean age was 36±5.7 years, and eight (67%) were female. The baseline mean AHI was 24.75±9.51 events/hour, the nadir mean oxygen saturation during sleep (SpO2 ) was 83.6±3.8%, the mean ESS score was 16±4, the mean forced expiratory volume in one second (FEV1 ) was 2.66±0.35 L, the mean forced vital capacity (FVC) was 3.23±0.45 L, the mean total lung capacity (TLC) was 4.97±1.19 L, the mean expiratory reserve volume (ERV) was 0.5±0.46 L, the mean residual volume (RV) was 1.46±0.91 L, the mean adjusted diffusing lung capacity for carbon monoxide (DLCO Adj) was 22.71±5.22 mL/mmHg/min, the mean adjusted diffusing lung capacity corrected for alveolar volume (DLVA Adj) was 5.61±0.90 mL/mmHg/min and the mean 6MWT was 293±49 m. Post surgery (12±2 weeks), the mean BMI decreased from 45.5 kg/m 2 to 39.7 kg/m 2, with a clinically significant improvement in AHI, ESS score, nadir SpO2, FEV1, FVC, TLC, ERV, RV, DLCO Adj, DLVA Adj and 6MWT ( p <0.05). Conclusion: Bariatric surgery improves sleep apnoea and lung function and reduces daytime somnolence.